The water balance of Lake Victoria: towards an accessible and updateable model - Murray-Williams, Róisín (Cranfield University, 2009)
Lake Victoria is the world’s second largest fresh water lake and with a basin spanning five countries the livelihoods of 30 million people depend upon its waters. Many water balance studies have been carried out yet there are often great difficulties in accurate data collection. This study aims to provide an accessible and easily updateable tool for modelling the water balance of Lake Victoria using publically available data. The study also investigates possible future lake level behaviour and the impact that water level fluctuations has on key stakeholders in the basin. In this study lake levels are successfully modelled from 1948-present using rainfall data available publically from the WMO and the NOAA using an equation modified from one developed by Nicholson et al, 2000. This therefore provides a tool which is accessible and updateable. Modelled lake levels underestimated some of the peaks in the observed record, however the correlation between observed and modelled levels was good, R2 = 0.8. As a departure around 2007/8 was observed, the performance of the NOAA data needs to be monitored over the coming years. Modelled future lake level behaviour varied considerably. The data from one GCM resulted in a significant increase in lake levels from 2010-2099 whereas the other two showed a slight decline on present levels. A challenge is posed by a high occurrence of inter-model disparities in East Africa. Whether a rise or decline is to be expected there are many stakeholders who will be affected in particular; water supply, fishing and hydro-electric generation directly and industry indirectly through power supply. Although there are a number of limitations of the model, this study provides a useful step in assessing the water level behaviour of a lake which is so important to the region.
Keywords: Climate Change; Impact on Stakeholders; Publicly Available Rainfall Data; fresh water lake; water balance; water level behaviour